2000
DOI: 10.1021/jp002334g
|View full text |Cite
|
Sign up to set email alerts
|

Sources, Sinks, and the Distribution of OH in the Lower Stratosphere

Abstract: Extensive measurement campaigns by the NASA ER-2 research aircraft have obtained a nearly pole-to-pole database of the species that control HO x (OH + HO 2 ) chemistry. The wide dynamic range of these in situ measurements provides an opportunity to demonstrate empirically the mechanisms that control the HO x system. Measurements in the lower stratosphere show a remarkably tight correlation of OH concentration with the solar zenith angle (SZA). This correlation is nearly invariant over latitudes ranging from 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 21 publications
2
46
1
Order By: Relevance
“…Low NO further reduces OH concentrations due to Reaction (R3). OH concentrations in this air mass are up to a factor of four smaller than those observed in the compact OH vs. solar zenith angle relation reported by Hanisco et al (2001) for similar altitudes.…”
Section: Aircraft Measurements Of Ohcontrasting
confidence: 64%
See 2 more Smart Citations
“…Low NO further reduces OH concentrations due to Reaction (R3). OH concentrations in this air mass are up to a factor of four smaller than those observed in the compact OH vs. solar zenith angle relation reported by Hanisco et al (2001) for similar altitudes.…”
Section: Aircraft Measurements Of Ohcontrasting
confidence: 64%
“…This approach used with our data results in negative ozone values throughout much of the troposphere for most of our tropical soundings. Hanisco et al (2001). The red circle indicates air masses from the West Pacific with extremely low ozone and OH.…”
Section: Ozone Profile Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The update includes a revised formulation of the system of differential equations, a new training method based on model results of the ATLAS Chemistry and Transport Model 1981, 1987, 1991, 2001, 2004, 201210 February 200915 February 20101 March 1984, 198910 March 1980, 200515 March 1983, 1986, 1988, 1998, 2000, 2002, 2003, 200824 March 201130 March 1982, 1990, 1992, 1993, 1994, 1995, 1996, 1997, 2014No stable vortex 1985, 1999 and an extension from a single level to the vertical range in which polar ozone depletion is observed.…”
Section: Discussionmentioning
confidence: 99%
“…The mixing ratio [OH] day is modeled by assuming Figure 4 shows that this is a sufficiently good assumption, partly due to the fact that the mixing ratios of OH are relatively similar in the Northern and Southern hemispheres. In conditions not disturbed by heterogenous chemistry on PSCs, it can be shown that the stratospheric OH abundance is in relatively good approximation a linear function of the solar zenith angle, mostly independent from the concentrations of other species (Hanisco et al, 2001). In addition, the average solar zenith angle in the vortex is in good approximation a linear function of FAS.…”
Section: Term Fmentioning
confidence: 99%